THE PECULIARITIES OF THE USE OF VOWEL SOUNDS IN THE SPEECH OF THE KARAKALPAKS OF SURKHANDARYA - Prekeeva, Amangul (SCIENCE and SOCIETY, 2026)
The article compares vowel sounds in the Surkhandarya Karakalpak language with the Karakalpak literary language and analyzes their usage.
Keywords: Turkic languages; Karakalpak literary language; Surkhandarya Karakalpak language; Kipchak dialect; vowel sounds; law of vowel harmony; diphthong; global problem